AL-MAQASHID AL-SYARIAH DALAM KONFIGURASI HUKUM ISLAM - Ahmad Ghazali Hb (Universitas Islam Negeri Antasari Banjarmasin, 2014)
Islamic law is the phenomenon that has strong relationship with the development in society, especially Islamic society. As we know, Islamic law (fiqh) constitutes outcome of the process of continuous development during the spread of Islam in the few centuries ago.Recently, Islamic law deals with the socio-cultural dynamics of society which always move. It requires updating the concept and formulation of Islamic law. For respond the socio-cultural dynamics, it is needed a better meaning to the Al-Maqashid Al-Syariah.